1984
DOI: 10.1002/art.1780270610
|View full text |Cite
|
Sign up to set email alerts
|

Mitogenic effects of hydroxyapatite and calcium pyrophosphate dihydrate crystals on cultured mammalian cells

Abstract: Synthetic hydroxyapatite (HA) crystals in 1 % serum stimulated ' H thymidine uptake into quiescent canine synovial fibroblasts and human foreskin fibroblast cultures, as did 10% serum. The onset of stimulation and peak uptake of thymidine after crystal addition were delayed by 2-3 hours as compared with the effects produced by 10% serum. Stimulation of 'H thymidine uptake was proportional to the serum concentration used. HA crystals (50 pglml) stimulated nuclide uptake at each serum concentration used. 3H thym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
69
0
1

Year Published

1984
1984
2009
2009

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 128 publications
(73 citation statements)
references
References 22 publications
3
69
0
1
Order By: Relevance
“…However, it is important to remember that osteolytic membranes contain a large percentage of both types of cells, and fibroblasts are capable of reacting to particulate debris by secreting a variety of proteases and cytokines which are capable of stimulating bone resorption and osteolysis [32,34]. Other studies have shown that human neonatal fibroblasts have been an excellent model for studying the responsiveness to HA particulates [9,10,12,13,16,20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is important to remember that osteolytic membranes contain a large percentage of both types of cells, and fibroblasts are capable of reacting to particulate debris by secreting a variety of proteases and cytokines which are capable of stimulating bone resorption and osteolysis [32,34]. Other studies have shown that human neonatal fibroblasts have been an excellent model for studying the responsiveness to HA particulates [9,10,12,13,16,20].…”
Section: Discussionmentioning
confidence: 99%
“…Crystals obtained from patients with this syndrome have been shown to induce cellular proliferation and the secretion of prostaglandins and proteases in synovial cells and macrophages [ 11,12,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…A model system of human foreskin fibroblast (HF) cultures was used for these experiments since HF responses to BCP crystals have been shown to be similar to those of synovial fibroblasts (5). HF cultures were established from explants and transferred as described previously (28).…”
Section: Cell Culturementioning
confidence: 99%
“…BCP crystals themselves are at least partly responsible for such proliferation since they stimulate cell replication in vitro (5). Increased cellularity in the synovial lining enhances the capacity for secretion of cytokines, which may promote chondrolysis.…”
mentioning
confidence: 99%
See 1 more Smart Citation